Atomic resolution snapshot of Leishmania ribosome inhibition by the aminoglycoside paromomycin - Moran Shalev-Benami (Nature Portfolio, 2017)
Leishmaniasis is a parasitic disease transmitted by the bite of infected sand flies. Here the authors describe an atomic resolution cryo-EM structure of the Leishmania ribosome in complex with the recently approved drug paromomycin (PAR) and highlight conserved elements in the drug binding pocket that mediate PAR deleterious effects on the parasite.